Redox Regulation of Phosphatase and Tensin Homolog by Bicarbonate and Hydrogen Peroxide: Implication of Peroxymonocarbonate in Cell Signaling - Vu Hoang Trinh; Jin-Myung Choi; Thang Nguyen Huu; Dhiraj Kumar Sah; Hyun-Joong Yoon; Sang-Chul Park; Yu-Seok Jung; Young-Keun Ahn; Kun-Ho Lee; Seung-Rock Lee (MDPI AG, 2024)
Phosphatase and tensin homolog (PTEN) is a negative regulator of the phosphoinositide 3-kinases/protein kinase B (PI3K/AKT) signaling pathway. Notably, its active site contains a cysteine residue that is susceptible to oxidation by hydrogen peroxide (H2O2). This oxidation inhibits the phosphatase function of PTEN, critically contributing to the activation of the PI3K/AKT pathway. Upon the stimulation of cell surface receptors, the activity of NADPH oxidase (NOX) generates a transient amount of H2O2, serving as a mediator in this pathway by oxidizing PTEN. The mechanism underlying this oxidation, occurring despite the presence of highly efficient and abundant cellular oxidant-protecting and reducing systems, continues to pose a perplexing conundrum. Here, we demonstrate that the presence of bicarbonate (HCO3−) promoted the rate of H2O2-mediated PTEN oxidation, probably through the formation of peroxymonocarbonate (HCO4−), and consequently potentiated the phosphorylation of AKT. Acetazolamide (ATZ), a carbonic anhydrase (CA) inhibitor, was shown to diminish the oxidation of PTEN. Thus, CA can also be considered as a modulator in this context. In essence, our findings consolidate the crucial role of HCO3− in the redox regulation of PTEN by H2O2, leading to the presumption that HCO4− is a signaling molecule during cellular physiological processes.